Knowledge and Attitude towards Blood Donations among Bachelor Level Students of Selected College in Bharatpur, Chitwan - Sharma, Nita; Pandey , Madhu Kumari; Sapkota, Devi Kumari; Parajuli, Sumitra (International Journal of Silkroad Institute of Research and Training, 2025)
Background: Blood donation involves the collection, testing, preparation, and storage of blood and its components. It is crucial to the healthcare system, enabling many medical procedures. This study " aimed to assess the knowledge and attitudes of bachelor-level students at Saptagandaki Multiple Campus in Bharatpur-10, Chitwan. Method: A Descriptive Cross-Sectional research design was used among 109 students of Saptagandaki Multiple Campus, Bharatpur. A non-probability purposive sampling technique was used to select samples. Data collection was done from July 16 to July 26, 2024, by using structured self-administered questionnaire and analyzed using Statistical Package for the Social Science (SPSS) version 20 with descriptive and inferential statistics. Result: Study finding revealed that among 109 students, mean age of students was 20.3 years. More than half (62.4%) were above 20 years of age. Around two-third (64.2%) of the students were female. Over half (55%) of the students had poor knowledge, 39.4% of the students had moderate level Knowledge and only few (5.5%) of the students had good knowledge and more than half (53.2%) of the students had a positive attitude towards blood donation. Blood donation knowledge was significantly associated with sex of bachelor level student. Conclusion: This study concluded that only few of the students have good knowledge and more than half of students have positive attitude regarding blood donation. Thus, proper educational programs should be conducted to increase awareness regarding blood donation and convert positive attitude into actual performance.